Dengue Co-Infection Microfilaria Presenting with Intestinal Obstruction: A Case Report - Kumar, A; Manchanda, S; Panda, PK; Jain, M; Kumar, V; Biswas, Ashutosh (Journal of Bangladesh College of Physicians and Surgeons, 2018)
In the recent years morbidity caused by dengue epidemic has been devastating. Confection of dengue malaria and filaria has been reported in literature where in filarial antigen was detected in the patient. Concurrent infection by dengue and filaria with high parsetemic microfilariae load in a single individual is very rarely known. The varied clinical profile in dengue is multifactorial and concurrent co-infection may be one of them. Here in this case of concurrent infection with dengue and filarial, the patient presented with intestinal obstruction which responded dramatically with diethylcarbamizine while other clinicalsyndrome took a long time. Furthermore, if single vector can harbour both the infectious agent, the etiopathogenesis may completely take a different turn and at times project alarming condition. J Bangladesh Coll Phys Surg 2019; 37(1): 35-38